2018
DOI: 10.1186/s13104-018-3653-6
|View full text |Cite
|
Sign up to set email alerts
|

Late antenatal care initiation: the case of public health centers in Ethiopia

Abstract: ObjectiveThe aim of this study was to determine the magnitude of late initiation of antenatal care visit and associated factors among antenatal care follow up women in Tselemte district health facilities. The data were obtained at health facilities level in a single survey within 1 month and there is no continuation part of this study or previously published part elsewhere.Results60.5% of women were late to initiate the first antenatal care visit. Time constraint with household activity (24.4%), distance to he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
20
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 12 publications
6
20
1
Order By: Relevance
“…It might be due to in developing countries especially in Ethiopia mothers are responsible and preoccupied in routing house hold activities and giving care for their kids, so they may get difficult in representing another person who gives care for the kids and the house hold activities. This evidence was confirmed by time constraint with household activity was one of the main reason for late ANC in Ethiopia [11]. In the other hand the current study identified women who recognized their pregnancy at third months or late were attending late than those who recognized their pregnancy before 3 months.…”
Section: Main Textsupporting
confidence: 68%
See 1 more Smart Citation
“…It might be due to in developing countries especially in Ethiopia mothers are responsible and preoccupied in routing house hold activities and giving care for their kids, so they may get difficult in representing another person who gives care for the kids and the house hold activities. This evidence was confirmed by time constraint with household activity was one of the main reason for late ANC in Ethiopia [11]. In the other hand the current study identified women who recognized their pregnancy at third months or late were attending late than those who recognized their pregnancy before 3 months.…”
Section: Main Textsupporting
confidence: 68%
“…Though a study done in south Africa, indicated there was no effect of gestational age at first ANC visit on stillbirth outcomes [9], but evidence from New Zealand and south Africa implied late attending of ANC was highly related with still birth [5, 10]. To alleviate the problems related with attending late ANC at first visit, the Federal Ministry Health of Ethiopia is trying to implement the WHO recombination focused ANC model, but many studied in the country indicated only about one-third of pregnant women were attending first ANC before the first 4 months of pregnancy [2, 7, 8, 11]. In addition, even though there are few evidences on the timing of antenatal care in Ethiopia, but the evidences did not addressed the determinants of early antenatal care visit in the country.…”
Section: Introductionmentioning
confidence: 99%
“…It might be due to in developing countries especially in Ethiopia mothers are responsible and preoccupied in routing house hold activities and giving care for their kids, so they may get difficult in representing another person who gives care for the kids and the house hold activities. This evidence was confirmed by time constraint with household activity was one of the main reason for late ANC in Ethiopia (11). In the other hand the current study identified women who recognized their pregnancy at third months or late were attending late than those who recognized their pregnancy before three months.…”
Section: Part Ii:determinates Of Late Anc Among Pregnant Women In Eassupporting
confidence: 69%
“…To alleviate the problems related with attending late ANC at first visit, the Federal Ministry Health of Ethiopia is trying to implement the WHO recombination focused ANC model, but many studied in the country indicated only about one-third of pregnant women were attending first ANC before the first four months of pregnancy (2,7,8,11). In addition, even though there are few evidences on the timing of antenatal care in Ethiopia, but the evidences did not addressed the determinants of early antenatal care visit in the country.…”
Section: Introductionmentioning
confidence: 99%
“…It might be due to in developing countries especially in Ethiopia mothers are responsible and preoccupied in routing house hold activities and giving care for their kids, so they may get difficult in representing another person who gives care for the kids and the house hold activities. This evidence was supported by a study done in Ethiopia which confirmed time constraint with household activity was one of the main reason for late ANC at first visit (11).…”
Section: Discussionsupporting
confidence: 59%